Environmental Assessment - The Inspection Panel (World Bank, Washington, DC, 2017)
The Inspection Panel, the World Bank’s independent accountability mechanism, has released the third report in its Emerging Lessons Series. The latest report identifies lessons from Panel cases related to environmental assessment (EA) issues. The Panel is an impartial fact-finding body, independent from the World Bank management and staff, reporting directly to the Board. In response to complaints from affected people, it has a mandate to review projects funded by the World Bank, investigate allegations of harm to people or the environment and review whether the Bank followed its operational policies and procedures. Of the 34 cases the Panel has investigated since it was created by the Bank’s Board of Executive Directors in 1993, 29 of them have involved environmental assessment issues. The Panel’s EA report identifies seven lessons that can be learned from those cases, and reaches five major conclusions. The Panel’s Emerging Lessons Series is meant to build institutional knowledge at the World Bank, enhance accountability and contribute to more effective development. The first two reports, on lessons from cases involving involuntary resettlement and indigenous peoples, were released in 2016. The fourth report in the series – on cases related to consultation, participation and disclosure of information – will be released in the fall of 2017.